Screening for SARS-CoV-2 infection in women prepared for elective Cesarean Section: A tertiary hospital study - Naz Mohammed Ahmed; Shahla Kareem Alalaf (Advanced Medical Journal)
Background and objectives: The SARS-CoV-2 infection is a major concern as universal testing should be undertaken to pregnant women due to the high danger of transmission from a pregnant woman to her newborn. This study was conducted to report the rate of SARS-CoV-2 infection in women admitted to hospital for purpose of preparation for elective cesarean section and to find out their risk factors and any histories of the infection previously.